Ginger protects against vein graft remodeling by precisely modulating ferroptotic stress in vascular smooth muscle cell dedifferentiation - Xiaoyu Yu; Weiwei Wu; Jingjun Hao; Yuxin Zhou; Deyang Yu; Wei Ding; Xuejuan Zhang; Gaoli Liu; Jianxun Wang (Journal of Pharmaceutical Analysis)
Vein graft (VG) failure (VGF) is associated with VG intimal hyperplasia, which is characterized by abnormal accumulation of vascular smooth muscle cells (VSMCs). Most neointimal VSMCs are derived from pre-existing VSMCs via a process of VSMC phenotypic transition, also known as dedifferentiation. There is increasing evidence to suggest that ginger or its bioactive ingredients may block VSMC dedifferentiation, exerting vasoprotective functions; however, the precise mechanisms have not been fully characterized. Therefore, we investigated the effect of ginger on VSMC phenotypic transition in VG remodeling after transplantation. Ginger significantly inhibited neointimal hyperplasia and promoted lumen (L) opening in a 3-month VG, which was primarily achieved by reducing ferroptotic stress. Ferroptotic stress is a pro-ferroptotic state. Contractile VSMCs did not die but instead gained a proliferative capacity and switched to the secretory type, forming neointima (NI) after vein transplantation. Ginger and its two main vasoprotective ingredients (6-gingerol and 6-shogaol) inhibit VSMC dedifferentiation by reducing ferroptotic stress. Network pharmacology analysis revealed that 6-gingerol inhibits ferroptotic stress by targeting P53, while 6-shogaol inhibits ferroptotic stress by targeting 5-lipoxygenase (Alox5), both promoting ferroptosis. Furthermore, both ingredients co-target peroxisome proliferator-activated receptor gamma (PPARγ), decreasing PPARγ-mediated nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 1 (Nox1) expression. Nox1 promotes intracellular reactive oxygen species (ROS) production and directly induces VSMC dedifferentiation. In addition, Nox1 is a ferroptosis-promoting gene that encourages ferroptotic stress production, indirectly leading to VSMC dedifferentiation. Ginger, a natural multi-targeted ferroptotic stress inhibitor, finely and effectively prevents VSMC phenotypic transition and protects against venous injury remodeling.